Memasyarakatkan Ilmu Merintis Kampus Barakah: Pengalaman Universiti Islam Sultan Sharif Ali (UNISSA): Publicising Knowledge to Evolve Barakah (Blessed) Campus: The Experience of Universiti Islam Sultan Sharif Ali (UNISSA) - Haji Mumin, Nurol Halimatulwara’; Shamsu, Lilly Suzana (‘Abqari Journal, 2019)
Universiti Islam Sultan Sharif Ali (UNISSA) has intensively and progressively offered academic or non-academic programmes that are based on pure Islamic studies. Thus, this research aims to share the practiced of UNISSA and its relentless efforts in instilling Islamic values for all courses and activities offered, as well as its persistence attempt in transferring this knowledge to public. The researchers will examine UNISSA’s academic curriculum and co-curriculum which enhanced academic excellence and also building human capacity amongst its students to be ummah’s future leaders. Moreover, this paper will also highlight a number of activities held by various disciplines and still integrated with the objective of serving the ummah. Thus, inculcate exemplary personality is inevitably understood as UNISSA’s future investment through promoting volunteer culture into UNISSA’s graduates. Library research methodology was used to gather data and information. Then, researchers will critically analyse it and do narrative approach with detailed explanation for some of its outstanding activities. This is to show UNISSA’s efforts in spreading Barakah Campus through its activities. To conclude, this paper will also highlight that reducing the gap between university and public is also one of the most important aspects that lead barakah to UNISSA. ABSTRAK UNISSA ditubuhkan dengan dasar program-program yang ditawarkan adalah berteraskan pengajian agama Islam tulen. Program yang dimaksudkan meliputi program-program akademik dan program non-akademik. Kertas ini berhasrat untuk mengongsikan pengalaman UNISSA yang tegar berusaha mengangkat dan melestarikan elemen-elemen pendidikan Islam dalam pengajian, sekali gus mengupayakannya untuk sampai kepada masyarakat umum. Kajian ini akan meneliti kurikulum dan ko-kurikulum yang disediakan oleh UNISSA di mana ia tidak hanya menyasarkan kecemerlangan akademik tetapi pembinaan jati diri pelajar sebagai pemimpin ummah masa depan. Di samping itu, kertas juga akan menelusuri kegiatan-kegiatan yang signifikan dalam berbagai tema namun memiliki matlamat yang satu iaitu berbakti kepada ummah. Penerapan sahsiah yang unggul dan jitu ini merupakan pelaburan masa depan untuk kelangsungan budaya sukarela dalam kalangan lulusan UNISSA. Kertaskerja ini akan menggunakan metodologi deskriptif dan naratif yang dihuraikan dalam bentuk kritis dengan menumpukan perincian kepada beberapa kegiatan yang signifikan. Perbincangan mengenai elemen-elemen tertentu ini akan dilakukan untuk meninjau kapasiti UNISSA dalam merintis kampus barakah. Hasil kajian pula akan menjelaskan bahawa upaya dan ikhtiar memasyarakatkan ilmu agama tanpa dibatasi tembok kampus adalah ciri-ciri yang akan mengundang barakah kepada UNISSA.